2021
DOI: 10.1038/s41698-021-00154-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic roles of inflammasomes in inflammatory tumor microenvironment

Abstract: The inflammatory tumor microenvironment has been known to be closely connected to all stages of cancer development, including initiation, promotion, and progression. Systemic inflammation in the tumor microenvironment is increasingly being recognized as an important prognostic marker in cancer patients. Inflammasomes are master regulators in the first line of host defense for the initiation of innate immune responses. Inflammasomes sense pathogen-associated molecular patterns and damage-associated molecular pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 144 publications
(255 reference statements)
1
22
0
Order By: Relevance
“…To overcome these limitations, multiple means of performing subtyping of these cases are being investigated, with many approaches focusing on the presence of tumour infiltrating lymphocytes (TILs) given that an enhanced presence of certain TILs may indicate an improved prognosis and response to immunotherapy [17,18]. This may not be surprising considering that lymphocytic infiltration is a major immunological defence against tumour cells in solid tumours, especially in the microenvironment where inflammatory activity plays a key role in initiating an appropriate immune response [19,20]. In particular, several studies have shown that the number and type of TILs are prognostic indicators for disease-free survival in numerous malignancies, including CRC, and are also associated with the response of a tumour following treatment with traditional immunotherapy [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations, multiple means of performing subtyping of these cases are being investigated, with many approaches focusing on the presence of tumour infiltrating lymphocytes (TILs) given that an enhanced presence of certain TILs may indicate an improved prognosis and response to immunotherapy [17,18]. This may not be surprising considering that lymphocytic infiltration is a major immunological defence against tumour cells in solid tumours, especially in the microenvironment where inflammatory activity plays a key role in initiating an appropriate immune response [19,20]. In particular, several studies have shown that the number and type of TILs are prognostic indicators for disease-free survival in numerous malignancies, including CRC, and are also associated with the response of a tumour following treatment with traditional immunotherapy [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanisms are still complex and uncovered, pro-coagulable state may produce a suitable milieu for cancer progression by recruitment of pro-metastatic leukocytes, adhesion to the endothelium, transendothelial migration, and restriction in natural killer cell-mediated clearance of micrometastasis [17,18]. Accumulating evidence showed that abnormal in ammation and oxidative stress are key factors to the development of heart failure, and those also play important roles in cancer progression and thrombus formation [19][20][21][22][23]. The in ammatory microenvironment is now recognized as an important participant or a regulator of all stages of tumor development, from an early stage of carcinogenesis to tumor promotion and metastatic spread to distant organs [22].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence showed that abnormal in ammation and oxidative stress are key factors to the development of heart failure, and those also play important roles in cancer progression and thrombus formation [19][20][21][22][23]. The in ammatory microenvironment is now recognized as an important participant or a regulator of all stages of tumor development, from an early stage of carcinogenesis to tumor promotion and metastatic spread to distant organs [22]. Regarding to thrombus formation, Gomes et al reported that blockade of IL-1 receptor abolished the neutrophil extracellular traps-dependent prothrombotic state and attenuated cancer-associated thrombosis in murine breast cancer model [23].…”
Section: Discussionmentioning
confidence: 99%
“…This establishes an inflammatory microenvironment, which promotes cancer progression and metastasis. The tumor-infiltrating immune cells, such as neutrophils, dendritic cells, and TAMs, further promote the secretion of IL-1β in the tumor microenvironment [ 27 ]. IL-1β secretion also contributes to angiogenesis by promoting the release of cytokines such as vascular endothelial growth factor (VEGF), macrophage-inflammatory protein-2 (CXCL2), and hepatocyte growth factor (HGF).…”
Section: Nlrp3 Inflammasome Activation and Its Role In Inflammatory Disordersmentioning
confidence: 99%
“…IL-1β has also shown to promote proliferation in cancer cells by activating several oncogenic signaling pathways [ 8 , 28 , 29 , 30 ]. In addition, extracellular ATP released from damaged tumor cells upon anti-cancer treatment also induces NLRP3 inflammasome activation [ 27 ]. Studies have suggested the role of IL-18 in the polarization of T cells toward Th1 or Th2 cells by inducing IL-17 expression in Th17 cells in certain types of cancer, while the role of IL-18 in tumor progression has not been fully elucidated yet [ 27 ].…”
Section: Nlrp3 Inflammasome Activation and Its Role In Inflammatory Disordersmentioning
confidence: 99%